2012
DOI: 10.1063/1.4750250
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle formation in a cavitation bubble after pulsed laser ablation in liquid studied with high time resolution small angle x-ray scattering

Abstract: CdSe quantum dots-poly(3-hexylthiophene) nanocomposite sensors for selective chloroform vapor detection at room temperature Appl. Phys. Lett. 101, 173108 (2012) An "edge to edge" jigsaw-puzzle two-dimensional vapor-phase transport growth of high-quality large-area wurtzite-type ZnO (0001) nanohexagons Appl. Phys. Lett. 101, 173105 (2012) Ti-doped hematite nanostructures for solar water splitting with high efficiency J. Appl. Phys. 112, 084312 (2012) Near-infrared enhanced carbon nanodots by thermally assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
177
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(191 citation statements)
references
References 24 publications
13
177
1
Order By: Relevance
“…Further, the influence of excess vacancies on precipitation during cooling needs to be explored. This can be done by adapting the cooling rates at high temperature, which influence the excess vacancy concentration due to annihilation on defects.SAXS is a useful tool to monitor precipitation phenomena during fast time and temperature changes given that a sufficiently high electron density contrast between the precipitate and matrix exists [4,8,10]. SAXS provides the means to collect information on the size and volume fraction of the precipitates that can then be directly compared to predictions of thermodynamic-based precipitation models [11,12].…”
mentioning
confidence: 99%
“…Further, the influence of excess vacancies on precipitation during cooling needs to be explored. This can be done by adapting the cooling rates at high temperature, which influence the excess vacancy concentration due to annihilation on defects.SAXS is a useful tool to monitor precipitation phenomena during fast time and temperature changes given that a sufficiently high electron density contrast between the precipitate and matrix exists [4,8,10]. SAXS provides the means to collect information on the size and volume fraction of the precipitates that can then be directly compared to predictions of thermodynamic-based precipitation models [11,12].…”
mentioning
confidence: 99%
“…This may be a unique feature of the cavitation bubble induced by liquid-phase laser ablation, since the deformation of the cavitation bubble is not observed when it is produced by an ultrasonic power [26,27]. Since it has been found that the growth field of nanoparticles in liquid-phase laser ablation is the inside of the cavitation bubble [36][37][38][39][40], the present experimental results may explain the origin of the high zeta potential of the colloidal solution synthesized by liquid-phase laser ablation. …”
Section: Discussionmentioning
confidence: 60%
“…The experimental results are consistent with a model calculation which assumes free charges on the gas-liquid boundary. Since it has been shown that the growth field of nanoparticles in liquid-phase laser ablation is the inside of the cavitation bubble [36][37][38][39][40], it is suggested that the origin of the high zeta potential of the colloidal solution synthesized by liquid-phase laser ablation is the electrical charges stored in the cavitation bubble.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental result clearly shows the growth of nanoparticles inside the cavitation bubble. The growth of nanoparticles inside the cavitation bubble has been confirmed by Ibrahimkutty and coworkers by small-angle x-ray scattering [13,14]. Another important knowledge obtained by our previous experiment is that nanoparticles are stored inside the cavitation bubble until its collapse.…”
Section: Introductionmentioning
confidence: 52%